Aditivos de formulação na formação de filmes isolados de etilcelulose. Estudos físico-químicos e morfológicos - Alves, Bruno R. V.; Reis, André L.; Hechenleitner, Ana A. W.; Pineda, Edgardo A. G.; Job, Aldo E. [UNESP]; Cavalcanti, Osvaldo A. (My University, 2009)
In this work were developed free films from Surelease®, additives α-GOS (alfa-glucooligosaccharide) and/or Tween® 80 in aqueous solution. It was obtained by Teflon plates casting process. The free films were characterized by thermal analysis (DSC and TGA), infrared spectroscopy (FTIR-ATR) and scanning electron microscopy (SEM). DSC and TG analysis showed that the additives do not influenced in the thermal stability of Surelease® films. SEM analysis observed homogeneous morphological characteristics and phase detachment absence. FTIR-ATR spectra were used to confirm the physical mixture between the components of films.
Formulation additives on formation of films isolated from ethylcellulose. Physicochemical and morphological studies
Keywords: α-glucooligosaccharide; Free films; Prebiotics; Surelease®